Health outcomes and budget impact projection of anti-PD-(L)1s in cancer care in Portugal - Costa, Luís; Alexandre, Teresa; Mansinho, André; Sousa, Rita; Vieira, Cláudia; Hughes, Robert; Roediger, Alexander; Pereira, Sónia Matos; Araújo, António (Frontiers in Public Health, 2023)
Introduction PD-[L]1 inhibitors revolutionized cancer treatment but challenge the affordability of health systems. This policy-focused model aimed to estimate the health and budget impact of anti-PD-(L)1s in Portugal and inform current discussions. Materials and methods The Health Impact Projection (HIP) model estimates clinical (life years, progression-free survival [PFS] years, and quality-adjusted life years [QALY] gained and adverse events [AEs] incurred) and economic (direct and indirect costs) outcomes in a world where cancer patients are initiating treatment with standard-of-care (SOC) versus SOC plus anti-PD-(L)1s over a 3-year time horizon. Indications included adjuvant and metastatic melanoma, non-small cell lung cancer (first and second line), metastatic triple-negative breast cancer, head and neck cancer, urothelial carcinoma, and renal cell carcinoma. Model inputs were based on publicly available literature data and expert opinion. Results The model estimated that, over 3 years, 7,773 patients would be treated with anti-PD-(L)1s, realizing a gain of 4,787 life years, 6,901 PFS years, and 4,214 QALYs and avoiding 399 AEs. The introduction of anti-PD-(L)1s had a projected average annual impact of ≈ €108 million and a share of 20% of total cancer medicines expenditure and 0.6% of total healthcare expenditure in 2021. Although higher disease management costs are expected for patients living longer with anti-PD-(L)1s and drug acquisition costs are considerable, that is partially offset by a reduction in end-of-life costs (€611,092/year) and costs associated with patient productivity lost to cancer (€9,128,142/year). Discussion This model highlights the significant survival and QoL benefit of anti-PD-(L)1s for cancer patients in Portugal, with a relatively low increased cost in total healthcare expenditure.